GAMBARAN PERSEPSI LANSIA TERHADAP PERAN PERAWAT DALAM PELAKSANAAN POSYANDU LANSIA DI DESA DILEM INSTITUT TEKNOLOGI DAN KESEHATAN MALANG WIDYA CIPTA HUSADA - Ririn Kurniawati (ITKM WIDYA CIPTA HUSADA, 2022)
The magnitude of the elderly population as well as the very rapid growth cause a variety of problems degenerative diseases. It the cause of the elderly need to get serious attention in improve health, by the presence of one Elderly Posyandu. The purpose of this study is to determine the Perceptions of The Elderly Of The Role Of Nurses In The Implementation Of Elderly Posyandu In The Village Glued The Working Area Of Puskesmas Kepanjen Malang Regency.The design of this research uses descriptive method withthe approach of cross sectional. The sampling technique of this research is cluster sampling of 100 respondents with the instrument in the form of questionnaire. This validity test using product moment pearson and reliability tests using cronbach's alpha. The results of the research show that the perception of the elderly to the nurse as educator 59%, care giver 79% , case manager 74%, consultant 69%, and obstacles in the implementation of elderly posyandu 66% of the elderly have good knowledge of, 53% of the elderly has a distance of home close to neighborhood health center, 53% of the infrastructure in the posyandu in good condition, 57% of communication is the nurse in the posyandu less,and 56% of existing services in the posyandu less. Conclusion from this study that the lack of communication and education of nurses,as well as the existing services in the elderly posyandu. suggestions that can given that is expected to increase the role of the nurse in communication and education, as well as increase the number of services there in the elderly posyandu